Balanced‐to‐unbalanced filtering power divider with compact size and high common‐mode suppression. Issue 8 (1st April 2018) - Luo, Ming; Tang, Xiao‐Hong; Lu, Di; Zhang, Yong‐Hong; Yu, Xu‐Min
Abstract : A compact balanced‐to‐unbalanced (BTUB) filtering power divider (FPD) to simultaneously realise the functions of power dividing, bandpass response, a BTUB transformer with high common‐mode suppression and good isolation between two output ports is proposed. This component is constructed by two half‐wavelength resonators and the special designed feeding‐line structure. For verification, an FPD working at 2.39 GHz is fabricated and measured. The measured results show good agreement with the simulation.